PEMANFAATAN EKSTRAK KASAR ENZIM PAPAIN PADA PROSES DEKAFEINASI KOPI ROBUSTA - Jeki Daisa; Evy Rossi; Rahma Dini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study was toget the best concentrations of crude extract papain enzyme to the caffeine content of coffee.This study used a Completely Randomized Design (CRD) with five treatments and four replications followed byDuncan’s New Multiple Range Test(DNMRT) test at 5% level. The treatment in this study were P0 (without the addition of crude extract enzyme papain), P1 (Papain enzyme crude extract 1 g/100 g weight of beans), P2 (Papain enzyme crude extract 3 g/100 g weight of beans), P3(Papain enzyme crudeextract 5 g/100 g weight of beans), and P4 (Papain enzyme crude extract 7 g/100 g weight of beans).The results of this study showed that papain enzyme concentration of crude extractwere significantly effected caffeine and moisture level.There was also significant effect of treatments on hedonic test for taste, aroma and color of product. The best treatment in this study was P2 with moisture, ash and caffeine level respectively 5.54%, 4.95%, and 1.02%. But, The sensory evaluation using  hedonic test on flavor, aroma, and color of coffee result the treatmets P4 was liked by panelists. Keywords: Robusta coffee, crude extract papain enzyme, and decaffeinetion process